Growth performance of blood cockle (Tegillarca granosa) within Kongkong Laut estuaries, Masai, Johor - Md Joni, Amirul Azuan; Mohamat Yusuff, Ferdius @ Ferdaus; Mohamed @ Mohd Ramli, Khairul Nizam; Mohd Kusin, Faradiella; Zulkifli, Syaizwan Zahmir (Universiti Putra Malaysia Press, 2019)
A non-coastal cockle farming area such as an estuaries zone might become an alternative for continuous and sustainable cockle supply in the future. The main objective of this research is to determine the growth and mortality rate of Tegillarca granosa (T. granosa) within an estuary area. Three cockle plots were allocated along the estuary area of Kongkong Laut (P1, P2, P3) based on the geographical area, from upper to lower part of estuaries. Cockle monitoring activity was conducted from August to December 2015 for both in-situ water parameters and the cockles’ growth increments. This study shows that within a brackish estuarine environment, the highest cockle growth increment was recorded within the highest water salinity trend area (26.92 ± 4.79 ppt; P2), with a shell increment of 2.70 ± 0.52 mm per month, while the lowest cockle growth increment was recorded within the lowest water salinity trend area (17.65 ± 5.73 ppt; P1) with the shell increment of 2.05 ± 0.86 mm per month. One-way ANOVA shows that there was significant difference (p<0.05) in growth increments among all sites of cockle plots, with significant positive correlation between the salinity level and the cockle’s growth rate (p<0.05, r=0.65). This indicates that salinity level within a brackish environment plays an important role towards cockle’s growth rate. Additionally, high turbidity level for a prolonged period leads to lower cockle survival rates within an area. However, further studies need to be done to look for other environmental factors that may affect cockle growth rate within an estuarine environment.